论唐代“大手笔”作家之声名消解与历史遮蔽 = Research on dispelling literary reputation and historical concealment of Tang “Dashoubi” writers - 曲景毅 Qu, Jingyi (2016)
本文以宋代《唐文粹》、明代《唐文鑒》、清代《唐駢體文鈔》（包括清代補遺的《唐文粹》）的編選作為參照，考察後世對唐代“大手筆”作家應用文寫作的接受情況：眾“大手筆”作家中張說、李德裕受到更多的認可，李嶠、蘇頲次之；宋、清兩朝“大手筆”作家受到一定的關注，明代似不受歡迎，他們受到後世青睞的多為其頌銘碑誌論等文體，愈往後被選錄作品的文學性越強，而佔其文章數量頗多的制誥表章，則逐漸消失在編選者的視野之中。文章進一步探討“大手筆”作家在文學史上聲名消解與歷史遮蔽的原因：由於文學觀念的轉移、政事掩蓋文學、人品影響文品、創作本身的缺憾及作品的散佚，使得“大手筆”作家之文學聲名逐漸消解，於现代文學史的敘述中被遮蔽。In Tang dynasty there are 16 writers to share “dashoubi” (大手筆，Great hand with the pen) title and they have great impact on Tang literary world. The article discusses the reception of Tang “dashoubi” writers in the Song, Ming & Qing from three anthologies of the Tang prose according to Tangwen Cui(唐文粹, Elite of Tang Prose), Tangwen Jian(唐文鑒, Mirror of Tang Prose) & Tang Pianti wenchao(唐駢體文鈔, Selections of Tang Parallel Prose) and try to establish the reasons why their literary reputation decline in the later generations and how the reputation was historically concealed.